Durs Grünbein a Milano nel trentennale della caduta del Muro di Berlino: Anima poetica, europea, cosmopolita (Materiali di Estetica. Terza serie, 2020)
Thirty years after the fall of the Berlin Wall and three quarters of a century after the Ventotene Manifesto Durs Grünbein visits Milan, where he reads from his newest works and holds the very meaningful speech Mailand, der Bahnhof, die Freiheit dealing with freedom, responsibility and the ethics of literature. Starting from the presence of civil commitment in the works of the most distinguished contemporary German author, who experienced “die Mauer” and the consequences of the Iron Curtain, the present essay investigates how Grünbein’s poetry and essaystic production result in a source of inspiration for the civil society. Through the performative power of Grünbein’s words and rhetorical strategies the reader is confronted with an intellectual well aware of the problems of his time, whose poetry shows a bracing sense of political reality without neglecting formal aspects.
Keywords: Durs Grünbein; Poetry and civil commitment; Milan; the Berlin Wall; The Ventotene Manifesto